Development of E-Worksheet Based on Collaborative Learning on Environmental Change Material to Train Science Literacy Skills for Class X Highschool - Amalia Syafa'Madani, Wardah; Pratiwi Puspitawati, Rinie (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
Science literacy very important to trained in learning because it is needed in the process of solving problems in everyday life. This study aims to produce collaborative learning-based E-worksheet on Environmental Change Material to Train Grade X Students' Science Literacy Skills that are feasible based on validity, practicality and effectiveness. E-worksheet based on collaborative learning developed with 4D models include define, design, develop, disseminate. The targets in this study were 20 students of class X SMAN 1 Taman. The data were analyzed using validation sheet to determine the validity of E-worksheet, implementation observation sheet and response questionnaire to determine practicality, pre-test and post-test sheet to determine the effectiveness. The results showed that the E-worksheet based on collaborative learning to train science literacy skills was valid with a score of 98.7% in terms of didactic, construction and technical aspects. E-worksheet based on collaborative learning was also declared practical based on the implementation of 97.14% and the response results of 98.75% with very practical interpretation. E-worksheet based on collaborative learning is declared effective based on N-gain, which is an increase of 0.79 with high category and sensitivity of ≥0.30. The effectiveness is reviewed from the achievement of science literacy indicators, namely identifying scientific phenomena by 100%, formulating problems 89%, designing investigations 98%, analyzing the results of the investigation 81%, evaluating results of investigation 87% and drawing conclusions with score of 83% with very high interpretation and on the indicator of analyzing the results of nvestigation with high category.